PENGARUH HARD SKILL DAN SOFT SKILL TERHADAP KINERJA KARYAWAN (Studi pada PT. Telkom Kandatel Malang) - WIDAYANTI, RAHAYU (DINAMIKA DOTCOM, 2012)
The organizational competitive factors may challenge any humans who work for business organization. Public organization, however, only requires its human resource to give primary service. PT. Telkom Kandatel Malang is a public organization moving in the information and communication fields, and providing a telecommunication service and network. The employee of this company plays important role to give a quality service. Good service quality cannot be isolated from employeeâs hard skill and soft skill. These skills must be improved because the information and telecommunication technology will always develop.Â Â Â Â It is necessary to match their skills with the technological advance.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Research aims at (1) analyzing the simultaneous effect between hard skill and soft skill on employee performance; (2) analyzing the partial effect between hard skill and soft skill on employee performance; and (3) analyzing the dominant variable affecting employee performance. The employee of PT. Telkom Kandatel Malang is considered as respondent of research.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Interval data are used in this research. Primary data are collected through questionnaire given to 54 employees in some host locker at PT. Telkom Kandatel Malang. Two independent variables are analyzed, i.e. hard skill and soft skill. The dependent variable is employee performance. The collected data are analyzed with multiple linear regression analysis.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Result of research indicates that hard skill and soft skill have positive and simultaneous effect on employee performance. Partially, hard skill and soft skill variables have positive significant effect. Hard skill variable is found as the dominant variable for its effect on employee performance.Â Keywords: hard skill, soft skill, employee performance, and multiple regressionÂ Â Â Â